DIGITAL METAPHORS IN POPULAR SCIENTIFIC MEDICINE (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
The digital revolution has profoundly influenced not only medical research and practice but also the way medicine is communicated to the public. Popular scientific medical discourse increasingly relies on digital metaphors—such as “the genetic code,” “editing the book of life,” “the brain as a computer,” and “the body as a database”—to explain complex biomedical processes in familiar terms